PENGARUH RELIGIUSITAS, GENDER, DAN LOVE OF MONEY TERHADAP PERSEPSI MAHASISWA TERKAIT PENGGELAPAN PAJAK - Maulana, Gunawan Farhan; Purwasih, Desy (LPPM Universitas Putera Batam, 2024)
The purpose of this study is to analyze the influence of Religiosity, Gender and Love of Money on Student Perceptions Related to Tax Evasion. This type of research is a quantitative research with primary data sources. The population in this study is Pamulang University students with the Accounting Study Program with a Concentration in Taxation. The sample selection method used in this study was convenience sampling so that the final sample obtained was 94 students and rounded to 100 students. The data quality test was carried out using a validity and reliability test and using IBM SPSS25, after which a classical assumption test was carried out, namely a normality test, a multicollinearita test and a heteroscedasticity test, after which a hypothesis test was carried out. The results of this study show that Religiosity, Gender and Love of Money simultaneously affect Student Perception Related to Tax Evasion. It partially shows that Love of Money has an effect on Student Perception Related to Tax Evasion. As for Religiosity and Gender, it does not affect Student Perception Related to Tax Evasion carried out on students of Pamulang University Accounting Study Program with Tax Concentration. Keywords: Student Perception Related to Tax Evasion, Religiosity, Gender, Love of Money